M Cells: Intelligent Engineering of Mucosal Immune Surveillance - Dillon, Andrea; Lo, David D. (Frontiers in Immunology, 2019)
M cells are specialized intestinal epithelial cells that provide the main machinery for sampling luminal microbes for mucosal immune surveillance. M cells are usually found in the epithelium overlying organized mucosal lymphoid tissues, but studies have identified multiple distinct lineages of M cells that are produced under different conditions, including intestinal inflammation. Among these lineages there is a common morphology that helps explain the efficiency of M cells in capturing luminal bacteria and viruses; in addition, M cells recruit novel cellular mechanisms to transport the particles across the mucosal barrier into the lamina propria, a process known as transcytosis. These specializations used by M cells point to a novel engineering of cellular machinery to selectively capture and transport microbial particles of interest. Because of the ability of M cells to effectively violate the mucosal barrier, the circumstances of M cell induction have important consequences. Normal immune surveillance insures that transcytosed bacteria are captured by underlying myeloid/dendritic cells; in contrast, inflammation can induce development of new M cells not accompanied by organized lymphoid tissues, resulting in bacterial transcytosis with the potential to amplify inflammatory disease. In this review, we will discuss the life history of M cells and the open questions regarding their unusual biology.